Program Layanan Bimbingan Belajar Bagi Siswa Yang Berkesulitan Membaca di SD Kelas Rendah - Siti Lufiah Ramadani; Fatihaturosyidah; Tatang Suratno (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
This research is based on the observations of researchers in elementary schools in the research environment. At the beginning of the observation, the researcher found a phenomenon that was relevant to this study, namely that there were students in class III who had difficulty reading. The reading difficulties experienced such as difficulty reading words consisting of three or more syllables and experiencing errors in recognizing words such as omission, insertion, replacement, reversal of letters, and stammering. The formulation of the problem based on this phenomenon is how the tutoring that has been given by the teacher so far to students with reading difficulties and the design of the tutoring service program needed for students with reading difficulties. The focus of this research is that the researcher makes a recommendation for a tutoring service program according to the needs of students with reading difficulties at SD Negeri Cikande Permai class III. Qualitative approaches and case study methods are used in this study. This method is used with data collection techniques through observation, interviews, and documentation. From the findings that have been analyzed, it is found that students who have reading difficulties need a monthly tutoring service program in the form of a matrix and evaluation. So that the process of learning activities for students who have reading difficulties can be served and run well according to their needs.